2007
DOI: 10.1002/eat.20443
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of eating disorder diagnoses

Abstract: Objective: Data on the stability of eating disorder (ED) diagnoses (DSM-IV) over 12 years are presented for a large sample (N 5 311) of female eating disordered patients with anorexia nervosa (AN), bulimia nervosa (BN), and binge eating disorder (BED).Method: Assessments were made at the beginning of therapy and 2-, 6-, and 12-year follow-ups. Diagnoses were derived from the Structured Inventory for Anorexic and Bulimic Eating Disorders. Possible diagnostic outcome categories were AN, BN, BED, NOS, no ED, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 18 publications
2
68
3
Order By: Relevance
“…Reasons for the stronger prediction in AN could be greater homogeneity and greater stability over time in AN, both in terms of (non) migration to other diagnoses and lower remission rates. [34][35][36] This suggests strong maintaining factors, and our results indicate that generalized self-control may be one of them. Also, restrictive symptoms relate more to self-image in AN, i.e., symptoms are more ego-syntonic than in other ED groups and therefore less likely to change.…”
Section: Summary Of Results and Methodological Considerationsmentioning
confidence: 76%
“…Reasons for the stronger prediction in AN could be greater homogeneity and greater stability over time in AN, both in terms of (non) migration to other diagnoses and lower remission rates. [34][35][36] This suggests strong maintaining factors, and our results indicate that generalized self-control may be one of them. Also, restrictive symptoms relate more to self-image in AN, i.e., symptoms are more ego-syntonic than in other ED groups and therefore less likely to change.…”
Section: Summary Of Results and Methodological Considerationsmentioning
confidence: 76%
“…It remains true that BED is more likely to remit than other eating disorders, 58 (Agras et al, submitted for publication) but in spite of its remitting pattern, patients perceive the disorder as stable and enduring, often lasting over a decade. 57 Furthermore, the findings that certain specialized treatments targeting specific BED related psychopathology perform better in reducing binge eating than do nonspecific behavioral weight loss treatments 79,80 is not consistent with Stunkard's and Allison's hypothesis.…”
Section: Is Bed Simply a Marker For Psychopathology?mentioning
confidence: 95%
“…Cachelin et al 56 completed a small followup study of individuals with BED, and also found considerable variability in maintenance of the BED diagnosis at 6-month follow-up. Finally, Fichter and Quadflieg 58 longitudinally studied a large group of various eating disordered patients, including 60 BED patients. They found little evidence of diagnostic crossover between BED and AN.…”
Section: Longitudinal Studies Of Bed Diagnostic Statusmentioning
confidence: 99%
“…Some studies have shown that ED were subject to diagnosis crossover [34, 49,50] . This may have consequences on the interpretation of our results.…”
Section: Discussionmentioning
confidence: 99%